2021
DOI: 10.1002/mma.7464
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of a stage‐structure model with spatial heterogeneity

Abstract: A stage‐structure competition‐diffusion model with spatial heterogeneity is investigated in this paper. Under some suitable assumptions, the existence of spatially non‐homogeneous steady‐state solutions is established by investigating eigenvalue problems with indefinite weight and employing Lyapunov‐Schmidt reduction. The stability of spatially nonhomogeneous steady‐state solutions is obtained by analyzing the set of the spectrum of the associated infinitesimal generator. In particular, the global stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Note that m, M are independent of n, then m ≤ S n ≤ M for all n ∈ N and the claim holds. Hence, one can use the similar arguments as those of [8] together with (34) to prove that S n → S * > 0 uniformly onΩ, where S * satisfies (48), which implies that S * = F (x, E * , I * , R * ).…”
Section: Introduction Since Kemack and Mckendrickmentioning
confidence: 89%
See 1 more Smart Citation
“…Note that m, M are independent of n, then m ≤ S n ≤ M for all n ∈ N and the claim holds. Hence, one can use the similar arguments as those of [8] together with (34) to prove that S n → S * > 0 uniformly onΩ, where S * satisfies (48), which implies that S * = F (x, E * , I * , R * ).…”
Section: Introduction Since Kemack and Mckendrickmentioning
confidence: 89%
“…Therefore, it is of great significance to use mathematical models to study infectious diseases. In recent years, based on the fact that environmental heterogeneity and individual migration have a significant impact on the spread of disease and the permanence of populations [3,34], many scholars have made extensive and profound research by using mathematical models [1,2,8,14,20,26,30,31,38,40,43,45,48]. In 2008, Allen et al [2] proposed the following frequencydependent SIS (susceptible-infected-susceptible) epidemic reaction-diffusion system with space-dependent disease transmission rate β(x) and recovery rate γ(x):…”
Section: Introduction Since Kemack and Mckendrickmentioning
confidence: 99%
“…In this model the populations of predator and prey permanently oscillate for almost all positive initial conditions. Recently, there have been some excellent works on global dynamics of resource competitive models (see [4,5,11,16,17,19,24,22,25,30,31,32,33,34]), which are important in understanding of the mechanism of natural selection: the principle of competitive exclusion (see [1,3,10,26,27,28,35,36]) or the coexistence of competing species. For example, Volterra [29] observed that the coexistence of two or more predators competing for fewer prey resources is impossible.…”
mentioning
confidence: 99%